2022
DOI: 10.1111/1365-2656.13662
|View full text |Cite
|
Sign up to set email alerts
|

Seaweeds influence oyster microbiota and disease susceptibility

Abstract: A growing awareness of role that microbiota can play in mediating the effects of pathogens on hosts has given rise to the concept of the pathobiome. Recently, we demonstrated that the Pacific oyster mortality syndrome affecting Crassostrea gigas oysters is caused by infection with the Ostreid herpesvirus type 1 (OsHV‐1) followed by infection with multiple bacterial taxa. Here we extend the concept of this pathobiome beyond the host species and its bacterial microbiota by investigating how seaweed living in ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Bacterial taxa Colwelliaceae, Cyanobacteria and Rhodobacteraceae are indeed significantly associated with oyster families harbouring higher resistance to POMS [ 15 ]. Beyond members of the oyster microbiota, cohabitation of oysters with macroalgae mitigates their resistance to POMS by modifying microbiota composition and affecting transcriptional response to OsHV-1 infection [ 127 ]. We argue that modulating oyster physiology and immune system through microbial exposure is a promising way to increase resistance to pathogens.…”
Section: Implications For Applied Perspectivesmentioning
confidence: 99%
“…Bacterial taxa Colwelliaceae, Cyanobacteria and Rhodobacteraceae are indeed significantly associated with oyster families harbouring higher resistance to POMS [ 15 ]. Beyond members of the oyster microbiota, cohabitation of oysters with macroalgae mitigates their resistance to POMS by modifying microbiota composition and affecting transcriptional response to OsHV-1 infection [ 127 ]. We argue that modulating oyster physiology and immune system through microbial exposure is a promising way to increase resistance to pathogens.…”
Section: Implications For Applied Perspectivesmentioning
confidence: 99%
“…The family Pirellulaceae includes the well-reported genus Rhodopirellula, which comprises the majority of the isolated strains within this family [41]. Bacteria belonging to this genus have been detected in the soft tissues of oysters using molecular methods [26,42]. In the present study, 95% of the isolates were identified as R. baltica, which is in accordance with the well-known cosmopolitan distribution of this species, already found in macroalgae, mussel shell biofilm, marine sediments and also in the water column [8,31,43,44].…”
Section: Planctomycetota Isolationmentioning
confidence: 99%